Pinning-engineered YBa2Cu3Ox thin films - Mele P.; Crisan A.; Adam M.I. (Springer Verlag, 2023)
This chapter gives an overview on the pure and applied research performed on YBCO added with artificial pinning centers (APCs) over the past ten years. Several categories of APCs are described in terms of their dimensionality (nanorods, nanoparticles, nanolayers, segmented nanorods, and more), and experimental results are discussed under the framework of GinzburgLandau theory. YBCO films added with APCs offer outstanding pinning performance in a wide range of temperatures (4.277K) and magnetic fields (130 T). APC technology appears as mature approach, and practical application of coated conductors +APCs is soon expected on the large scale. 2017, Springer International Publishing AG.